Spatial-geographical analysis of smart growth indices in urban areas (Case study: Bushehr Port) - Hajar Jahanshahi; Hamidreza Varesi; Masoud Taghavei (تحقیقات کاربردی علوم جغرافیایی)
In fact, the growth of urban consciousness is a wise strategy to drive urban development and control dispersion and drive urban growth toward sustainability. The purpose of this study was to evaluate the rate of Bushehr city area in terms of growth indices. In this regard, this research is a goal-oriented, applied-developmental one, and a combination of documentary, analytical, causal and survey methods. Reliability of the research instrument based on Cronbach's alpha coefficient of the research was 0.749 which is higher than 0.7 and is appropriate. The statistical population of the study is Bushehr inhabitants which according to Cochran formula is estimated 384 samples. According to the statistical population, the questionnaire was distributed randomly among the citizens. In order to compare between two regions, T-test with two independent samples was used for evaluation of urban smart growth in District 1 and 2 of Bushehr. In this test, the first option to be considered is the significance level while the significance level or sig between the two regions is less than 0.05 indicates a significant difference between the two regions and vice versa. Significance level analysis (0.000) shows that there is a significant difference between the two regions in terms of urban smart growth. Meanwhile, the mean of Region 1 with 3.21 was higher than that of Region 2 with 2.86. Although there is a significant difference in Bushehr region in terms of smart growth indices, this difference is not significant and in general Bushehr regions are not in a good position in terms of smart growth indices.